Feasibility of outpatient management after intra-articular yttrium-90: comparison of two regimens. Issue 6257 (3rd January 1981) - Williams, P L; Crawley, J C; Freeman, A M; Lloyd, D C; Gumpel, J M
Abstract : In a study comparing two regimens of treatment after intra-articular irradiation of the knee with yttrium-90 one group of patients was allocated to bed rest for 48 hours in hospital and the other to mobilisation at home. Initially a Robert-Jones orthopaedic bandage was applied to the knee in all patients, serving as a semi-rigid splint, but as loss of isotope from the knee was appreciable in the mobilised patients, subsequent patients were sent home with the knee in a plaster-of-Paris cylinder. No difference in extra-articular spread or chromosomal damage was found between the patients sent home with their knee in a rigid splint and those treated by bed rest. Clinical outcome at three months was satisfactory in all three groups. These results show that rigid splinting is essential in reducing extra-articular spread of the isotope but that bed rest is not necessary. Increases in intra-articular pressure associated with quadriceps muscle activity combined with flexion of the knee may be the most important factor affecting extra-articular spread of isotope.